Co-administration of haloperidol does not alter anesthetic ketamine-induced go/no-go reversal learning impairments in rats - Fisher, Hayley (Kansas State University, 2019)
Ketamine, an NDMA receptor antagonist drug, is used as a general anesthetic in humans and animals because of its wide margin of safety and limited respiratory effects. However, the long-term effects of anesthetic ketamine exposure on behavior are largely unknown. Previously, our lab has found that three exposures to anesthetic ketamine (100 mg/kg) in rats improves go/no-go reversal learning, a task used to model behavioral flexibility. In the present study we sought to block the alterations in go/no-go reversal learning caused by anesthetic ketamine exposure by co-administering ketamine with haloperidol, a dopamine D2 receptor antagonist and classical anti-psychotic. In the study rats received intraperitoneal injections of haloperidol (1 mg/kg or 10 mg/kg) or vehicle co-administered with ketamine or saline to determine whether haloperidol co-administration could protect against ketamine-induced alterations in go/no-go reversal learning. Twelve days following the final injection the rats began go/no-go discrimination and reversal learning training. Haloperidol alone had no effects on discrimination or reversal learning. In contrast to our previous findings, ketamine impaired go/no-go reversal learning and haloperidol did not block this effect. It is possible that methodological differences between the present study and previous studies from our lab may have contributed to this discrepant finding, although more research is needed to isolate the cause of the opposite effect. These data show that haloperidol is not protective against ketamine’s effects when ketamine results in impaired go/no-go reversal learning. Other drugs, like clozapine or selective alpha-7 nicotinic agonist drugs, may be more promising candidates to block anesthetic ketamine’s effects on go/no-go reversal learning.
Keywords: Reversal learning; Haloperidol; Anesthetic ketamine